Heterogeneous template-dependent transcription dynamics of T7 RNAP revealed by single-molecule imaging - Sarah Zernia; Joëlle Deplazes-Lauber; Jonas Huber; Johannes Stigler (Proceedings of the National Academy of Sciences, 2025)
Bacteriophage T7 RNA polymerase (T7 RNAP) is commonly used for large-scale RNA synthesis in science and industry. Although T7 RNAP exhibits high processivity, its usage faces two major challenges: During initiation, the enzyme frequently aborts transcription, producing potentially immunogenic short RNA by-products; transient pausing during elongation facilitates premature termination, which leads to shorter transcripts and reduces the overall product yield. Here, we present a single-molecule high-throughput transcription assay using DNA curtains to study initiation, elongation, pausing, and termination of individual polymerases and examine what drives transcription aborts. We introduced two different promoter sites on the template DNA and found that transcription initiation is directly influenced by the DNA shape parameters of the initiation region downstream of the conserved promoter sequence. Furthermore, we showed that dimethyl sulfoxide can alleviate the effects of suboptimal initiation sequences. During elongation, we identified two sequence-dependent pause types that differ in length, of which the short pauses relate to ubiquitous pauses in bacterial polymerases. Longer pauses emerged by direct contact of the enzyme with a recognition motif on the template and were stabilized through interactions of the nascent RNA with the enzyme. These insights into transcriptional initiation and pausing highlight common impediments to the performance of the T7 RNAP transcription system.